MANAGEMENT OF SUPPLYCHAIN –CASE STUDY SCANIA PRODUCTION (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article shows the management of supply chain, from delivery logistics to distribu-tion logistics.There are description about effective factor management of supply chain, among others benchmarking. In the end of the article is case study –Scania Production.
Keywords: management of supply chain, delivery logistics, distribution logistics, ben-chmarking